A Comparative Study on Transgenic Animal Breeding and Patentability Analysis in India: Reference to Animal Husbandry in Biotechnology Industries - A, Dutta; E, Das (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Transgenic animal breeding or genetically modified animals are useful for various industries like the pharmaceutical industry, the agricultural industry, farming and medical research and development. In modern times the research on biotechnology and gene patent are frequently shows the urgency of development in the area of patent regimes. The United States and other developed country continue to expand their research on genetically-engineered animals and claims the patent protection. The paper aims to describes the process to evolve transgenic animals and the role in food industry. Furthermore, this article draws the development of animal patents in India and the issue regarding patent protection for transgenic animals. Lastly, this paper concludes the adequate and flexible legal framework to support the patent granting and patent protection for transgenic animals to enhance the scope of research and development in the biotechnology industries.